2017
DOI: 10.1093/ckj/sfx115
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease stage affects small, dense low-density lipoprotein but not glycated low-density lipoprotein in younger chronic kidney disease patients: a cross-sectional study

Abstract: BackgroundSmall, dense low-density lipoprotein (sd-LDL) and glycated LDL (g-LDL) have been associated with cardiovascular disease (CVD) in chronic kidney disease (CKD) in patients >60 years of age. Since young adult and paediatric patients have shorter exposure to Framingham-type risk factors, our study aims to determine whether younger CKD patients exhibit the same sd-LDL and g-LDL pattern.MethodsAfter ethics board approval, this cross-sectional study was conducted at two universities with 44 patients (mean ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…They determined whether younger CKD patients have the same sd-LDL and g-LDL-C pattern as adults with CKD. They demonstrated that only TG and sd-LDL were associated with CKD stages among young patients without Framingham-type CVD risk factors and suggested that lowering sd-LDL levels may be a potential target to improve the long-term CVD risk in young patients with CKD [165].…”
Section: Glycationmentioning
confidence: 99%
“…They determined whether younger CKD patients have the same sd-LDL and g-LDL-C pattern as adults with CKD. They demonstrated that only TG and sd-LDL were associated with CKD stages among young patients without Framingham-type CVD risk factors and suggested that lowering sd-LDL levels may be a potential target to improve the long-term CVD risk in young patients with CKD [165].…”
Section: Glycationmentioning
confidence: 99%
“…Increased prevalence of sdLDLs is common in CKD [48]. Importantly, it has been shown that the quantity of sdLDL particles is associated with the disease stage in both adult and young CKD patients [49,50]. In addition, sdLDL-cholesterol level was identified as an independent risk factor for CVD development in subjects with CKD [44].…”
Section: Small Dense Ldl In Obesity Diabetes and Chronic Kidney Diseasementioning
confidence: 99%
“…However, it is difficult to dissect the role of CKD from the cluster of risk factors that may accompany carotid atherosclerosis (e.g., hypertension, diabetes, dyslipidaemia and inflammation) in these patients (49)(50)(51). In this context, qualitative and quantitative lipid abnormalities have been reported in these patients (52)(53)(54)(55) and linked to both carotid atherosclerosis (55)(56)(57)(58) and CKD progression (59). Moreover, blood pressure, haemoglobin and several mineral metabolism parameters predict carotid atherosclerosis progression in CKD patients (60,61).…”
Section: From Carotid Atherosclerosis To Ckd Progression and CV Eventsmentioning
confidence: 99%